2006
DOI: 10.1111/j.1365-3083.2006.01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Single Nucleotide Polymorphism on the Expression of Human Tumor Necrosis Factor‐alpha

Abstract: Tumor necrosis factor (TNF)-alpha plays a prominent role in inflammations and is a proinflammatory cytokine that has been implicated in the pathogenesis of autoimmune and infectious diseases. Recent association studies have found that the TNF-alpha-857T allele was associated with several disorders. Here we demonstrate, with reporter genes under the control of the two allelic TNF-alpha promoters, that the minor allele -857T is a much stronger transcriptional activator than the major allele -857C in RAW264.7 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
1
26
1
Order By: Relevance
“…A more recent investigation of lipopolysaccharide-stimulated RAW 264.7 cells revealed that upon transfection of reporter genes under the control of the 2 TNF-857 alleles, TNF*-857T is a considerably stronger activator of transcription than is TNF*-857C. However, this result was not consistent with that found in a HeLa cell line, suggesting that depending upon additional factors, alleles of this polymorphism act in a cell-and tissue-specific manner (29).…”
Section: Discussioncontrasting
confidence: 54%
“…A more recent investigation of lipopolysaccharide-stimulated RAW 264.7 cells revealed that upon transfection of reporter genes under the control of the 2 TNF-857 alleles, TNF*-857T is a considerably stronger activator of transcription than is TNF*-857C. However, this result was not consistent with that found in a HeLa cell line, suggesting that depending upon additional factors, alleles of this polymorphism act in a cell-and tissue-specific manner (29).…”
Section: Discussioncontrasting
confidence: 54%
“…Although its functional role in AS has not yet been well established, variation in the TNFa gene may result in differences in the amount of TNF-a mRNA and protein produced, which may play some role in Table 2 Comparison for frequencies of genotypes between HLA-B27 ? AS patients classified by clinical subtypes and controls, n the pathogenesis of AS [11,12]. Several studies have attempted to investigate the relationship between susceptibility to AS and TNF-a polymorphisms in patients with AS [13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…healthy controls [10]. Variations in TNF-a production in individuals or in a tissue-specific manner could be explained by gene mutations or polymorphisms within the regulatory regions of TNF-a [11,12]. The TNF1/1 genotype at position -308 in HLA-B27 ?…”
Section: Introductionmentioning
confidence: 98%
“…To functionally test this hypothesis we generated allele specific reporter constructs, in which the firefly luciferase gene was placed under the regulation of the proximal TNFA promoter region. Two construct were generated; one included the common (C) allele, whereas the other harbored the rare (T) allele at the site corresponding to the -857th nucleotide position (Lv K 2006). Furthermore, the proximal part of the 3' untranslated region (3' UTR) of the TNFA gene was also cloned into both constructs, similarly as it was described by Denys et al (Denys A 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A piece of the proximal TNFA promoter was cloned into the pGL4.20 luciferase reporter plasmid (Promega, Madison, USA) similarly as it was described by Lv et al (Lv K 2006). For that a 1012 base pair (bp) piece of the TNFA regulatory region was amplified using the following primers:…”
Section: Generation Of the Tnfa Luciferase Reporter Constructsmentioning
confidence: 99%